OPTIMALISASI SOCIAL MEDIA MARKETING UNTUK MENINGKATKAN PENJUALAN PADA UMKM - Andreas Octavini, Nanda; Agustin, Maulina; Rahmawati, Yannisa; Sormin, Rahma Diani; Putri, Levina Rachmawati (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Social media has become an effective tool for promoting products and services, especially for micro, small, and medium enterprises (MSMEs). However, many MSME players, particularly those running angkringan-type businesses, still lack the knowledge and skills to use social media effectively to increase sales and expand customer reach. The objective of this community service activity is to enhance MSME players’ understanding of the importance of social media marketing, and to equip them with effective digital marketing strategies. The method employed involves training sessions that begin with a presentation on optimizing social media for marketing purposes, delivered by resource persons, and continue with practical sessions where MSME participants apply digital promotion techniques. The results of this activity indicate an improvement in participants' knowledge and understanding of social media marketing strategies, as reflected in their ability to implement the tools and techniques introduced during the training.